Population based study on the progress in survival of primarily metastatic lung cancer patients in Germany - Tzschoppe, Therese; Ohlinger, Julia; Vordermark, Dirk; Bedir, Ahmed; Medenwald, Daniel (Scientific reports, 2024)
Lung cancer is known for its high mortality; many patients already present with metastases at the time of diagnosis. The aim of this study is to assess the impact of new treatment strategies on the survival of primarily metastatic lung cancer patients and to analyze the differences in outcomes between non-small cell lung cancer (NSCLC) and small cell lung cancer (SCLC) patients. Population-based data, provided by the Robert-Koch Institute in Germany, was used and patients diagnosed between 2007 and 2018 were included in the study. We differentiated between NSCLC and SCLC patients and analyzed the survival over time for both sexes separately, using the Kaplan–Meier method. To evaluate survival advantages, we calculated multivariable hazard ratios. In total, 127,723 patients were considered for the study. We observed a moderate increase in survival over time. All patients showed an increased survival rate when undergoing chemotherapy. Minimal to no increase in survival was shown in NSCLC patients when receiving radiotherapy, whereas SCLC patients’ survival time did benefit from it. NSCLC patients receiving immunotherapy showed an increase in survival as well. It can be concluded that advancements in radiotherapy, the application of chemotherapy, and the introduction of immunotherapies lead to an increased survival time of both NSCLC and SCLC primarily metastatic lung cancer patients.